Bilateral tibial stress fracture in a young man due to hypercalciuric osteoporosis: a case report - AKYÜZ, GÜLSEREN DERYA (SPRINGER, 2006)
Osteoporosis is commonly thought of as a disease of postmenopausal women, and older men have a lower risk of fracture than women. A stress fracture is an overuse injury and an important cause of disability in the athletic population. Presented here is a 30-year-old healthy man with pain on the anterior surface of the bilateral tibia. He did not communicate any trauma or overuse activity. The neurologic and locomotor system examinations were normal. Radiological examinations revealed tibial stress fractures in both left and right tibia and he had low bone mineral density. Routine hematological tests, bone resorption and formation markers were normal, except for hypercalciuria. After analyzing the results of these tests, the patient was diagnosed with bilateral tibial stress fractures due to hypercalciuric secondary osteoporosis. Osteoporosis should be considered in the differential diagnosis of atraumatic insufficiency fractures, especially in young healthy adults.
Keywords: hypercalciuric osteoporosis; osteoporosis; osteoporosis in men; tibial stress fracture; young male osteoporosis; MEN; DIAGNOSIS; RISK